Debt behavior of different generations before and after COVID-19 - Maria A. Gagarina (Saratov State University, 2021)
The relevance of researching debt behavior in the context of the pandemic is associated with the need to understand the changes in the willingness of Russians to postpone the satisfaction of their needs and help others in the face of a worsening epidemiological, economic and social situation in the country. The aim of the study was to compare the debt behavior of the baby boomer generations X, Y and Z before and after the beginning of the pandemic. Research hypothesis, respondents interviewed prior to COVID-19 will have a lower willingness to lend and borrow, and willingness to fulfill obligations will remain unchanged, compared to respondents interviewed after COVID-19. Sample 1: interviewed from 2013 to January 2019, before the beginning of the COVID-19 pandemic in Russia, N = 390 (159 men, 217 women, 14 did not indicate gender), representatives of different generations. Sample 2: interviewed in 2020, N = 390 (201 men, 189 women), 17-70 years, corresponding in age and number of representatives of different generations to respondents from sample 1. Methods: questionnaire, including socio-demographic data and borrowing experience, "Debt behavior express inventory". For sample 2, additionally the experience of the COVID-19 pandemic and questionnaire "Attitude of the individual to the epidemiological threat" by T. A. Nestik. Results. For generations of baby boomers, X, Y, there are similar changes in readiness for debt behavior in all areas: borrowing, lending and fulfilling obligations. Compared to the respondents surveyed before the beginning of the pandemic, there are significantly higher values (Student's t-test, p <0.01) on the scale of "condemnation of borrowers" and significantly lower values on the "rationality of debt behavior" and "avoidance of debt" scales. The difference between generations in experiencing an epidemiological threat is the difference between generation Z and older generations. It is shown that the higher the fear of a worsening economic situation as a result of COVID-19 is, the lower the willingness to both borrow and lend is, and the higher the confidence in one's ability to cope with difficulties and empathy for others during the pandemic are, the greater the readiness to fulfill debt obligations is.